Adaptability factors and behavioral biases of investors in frontier markets: An adaptive market hypothesis perspective - Jannatunnesa Jannatunnesa; Nurul Shahnaz Mahdzan; Abu Hanifa Md Noman (PLoS ONE, 2026)
The Adaptive Market Hypothesis (AMH) suggests that investors are imperfect but adaptive, allowing behavioral biases to persist and evolve over time. However, empirical research on how adaptability factors influence these biases in stock investment remains limited, especially in frontier markets. This study examines the impact of adaptability factors on herding (HRD) and overconfidence (OVR) biases among individual investors in Bangladesh, a frontier market. Employing purposive sampling, data were collected through structured face-to-face and online questionnaire surveys from 640 retail investors on the Dhaka Stock Exchange (DSE). Data were managed using the Statistical Package for the Social Sciences (SPSS) and analyzed using SmartPLS 4.0 for Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that all the external adaptability factors ( social influence, consultation with financial advisors, and media ) positively influence herding, while the internal adaptability factors ( trading experience, self-reflection, and desire for learning ) positively influence overconfidence. Financial literacy negatively affects both biases. The study offers insights for policymakers, regulators, and investors on the cognitive and social elements driving biased investment decisions, especially in frontier markets. To the best of the authors’ knowledge, this study pioneers a market adaptability model incorporating novel variables, labelled ‘adaptability factors’, grounded in AMH and bounded rationality.